EFFECTS OF NIGELLA SATIVA ON VARIOUS PARAMETERS IN PATIENTS OF NON-ALCOHOLIC FATTY LIVER DISEASE - Hussain, Mazhar; Tunio, Ali Gul; Arain, Lubna Akhtar; Shaikh, Ghulam Serwar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Non-alcoholic Fatty Liver disease (NAFLD) is the most common cause of progressive liver disorders worldwide. Drug options are limited with varying results. Nigella sativa in the form of herbal medicine could be another option because of its strong historical background. The objective of the study was to evaluate the effect Nigella sativa on various parameters in patients of NAFLD. Methods: A randomized controlled trial was conducted at outpatient clinic of medical unit-1 of Sheikh Zayed Medical College/Hospital, Rahim Yar Khan, in which seventy patients of NAFLD were divided in to interventional and non-interventional groups. The interventional group was given cap Nigella sativa 1g twice a day while non-interventional group was given cap placebo in a same way for three months. Body weight, BMI, liver enzymes and ultrasound finding of fatty liver were assayed before and after treatment. Results: After 12 weeks treatment with Nigella sativa body weight decreased significantly from 86±13.8 to76±12.6 kg vs placebo (p=0.041). BMI also reduced significantly from 29.06±4.6 to 26.25±6.2kg/m2 vs placebo(p=0.012). There is remarkable reduction in aminotransferases level after treatment with Nigella sativa vs placebo (ALT: 78.05±5.52 to 52.6±5.65 IU/L vs 76.48±4.95-74.32±5.58 IU/L (p=0.036). AST: 65.54±4.56-44.56±5.52 IU/L vs 63.25±5.43-59.43±3.39 IU/L (p=0.021). There was overall 57.14 % patient had normal fatty liver grading on ultrasound after 12 weeks treatment with Nigella sativa as compared to placebo (p=0.002). Conclusion: Nigella sativa improves bio chemical and fatty liver changes in NAFLD patients. Its use in early stages of NAFLD is recommended in order to prevent its life-threatening complication. Keywords: NAFLD; Nigella sativa; Body weight; ALT; AST; Fatty liver grading